The Legend Of The Biblical Flood In The Folk Traditions Of Adzharia And In Georgian Population Of Turkey - Intskirveli, Eter (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Surprisingly enough, the motive of the Biblical Flood in Georgian folklore is the most widespread in Adzharia. This is, naturally, due to the fact that this region of Georgia is located close to the sea. While in various regions of Georgia the motives related to Noah’s Arc exist chiefly in the form of narrative, in the folklore and ethnographic material of Adzharia it is found not only as narrative, but also in rituals and folk traditions. One of such traditions is related to a spring meal – Ashura, which is derived from the Biblical story of Noah cooking soup with the remaining seeds and feeding the creatures in the Arc. In Achara the dish is made of about 40 species of plant seeds. Another ritual related to Noah’s Arc is Adzharian wedding tradition when the bride’s parents visit the groom’s family, bringing some sweets as a gift.